GERAKAN KEWIRAUSAHAAN SOSIAL BERBASIS BUDIDAYA ANGGREK (STUDI DAN REKONSTRUKSI KONSEP PADA BUDIDAYA ANGGREK PADMA ORCHID YOGYAKARTA) - Yuliani, Irma (Universitas Sebelas Maret, 2019)
This study aims to find the observations regarding community empowerment based on the orchid cultivation. In addition, this research attemps to construct the concept of community empowerment through a partnership pattern. The elements that have built the partnership include private sector, academics, government, and society. The existence of the private sector is believed to be able to encourage business development through adequate capital, the existence of the government is very important to ensure smooth empowerment and business traffic activities, and the existence of academics can support the development of empowerment and improvement in the quality of empowerment through research activities. Three main patterns are found in this partnership; first, the research development patterns; Second, marketing patterns and; Third, advocation patterns. These patterns are believed to be able to provide effective solutions and strategies so that orchid-based community empowerment activities can be carried out properly and sustainably.